Determinants of the Adoption of Digital Healthcare Systems in Corporate Companies in Selangor, Malaysia - Lin, Alysha Tung Hui; Kumar, Kavigtha Mohan (Journal of Entrepreneurship, Business and Economics, 2026)
The purpose of this paper is to investigate the factors influencing the adoption of digital healthcare systems in corporate companies across Malaysia. The study applies the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework to examine how technological and behavioral factors affect HR departments' adoption of digital healthcare platforms such as MiCare, HealthMetrics etc. The moderating role of company size was also examined and employee satisfaction as an outcome. This study targets employees in corporate companies of varying sizes, ranging from fewer than 5 employees to over 200 employees. Data was collected via online questionnaires from employees using digital healthcare systems. The extended UTAUT2 model includes 15 hypotheses testing relationships between performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, behavioral intention, actual use, and employee satisfaction. The study revealed that performance expectancy (β=0.45, p<0.001) was the strongest predictor of digital healthcare adoption, especially in large companies, while SMEs were more influenced by price value (β=0.41) and social influence (β=0.35). Company size significantly moderated these relationships, with large firms showing 15% stronger performance expectancy effects and SMEs demonstrating 25% greater price sensitivity. Behavioral intention strongly predicted both actual system use (β=0.58) and employee satisfaction (β=0.52), with adopters reporting 27% faster claims processing and 19% higher engagement in wellness programs, confirming the technology's dual benefit for operational efficiency and workforce well-being. The study identifies key adoption drivers and offers tailored strategies for HR leaders and tech vendors, recommending scalable solutions for SMEs and performance-driven tools for larger firms. Policymakers are encouraged to support adoption through subsidies and awareness campaigns. This research extends UTAUT2 by incorporating employee satisfaction as an outcome and company size as a moderator. It provides empirically validated guidelines for digital healthcare adoption in Malaysian corporate settings, addressing significant research gaps in the literature. Research Paper Keywords: Digital healthcare systems, Technology adoption, UTAUT2, Corporate HR, Malaysia, company size, Employee satisfaction Reference to this paper should be made as follows: Lin, A.T.H., & Kumar, K.A.M. (2025). Determinants of the Adoption of Digital Healthcare Systems in Corporate Companies in Selangor, Malaysia. Journal of Entrepreneurship, Business and Economics , 13 (1), 236–267.